(untitled) - Brenton, Chris (San Francisco, 2003)
Expertise is what makes hackers effective. It's what will make you effective, too, as you fight to keep them at bay. Mastering Network Security has been fully updated to reflect the latest developments in security technology, but it does much more than bring you up to date. More importantly, it gives you a comprehensive understanding of the threats to your organization's network and teaches you a systematic approach in which you make optimal use of the technologies available to you.
Keywords: Computer security,Computer networks,An ninh máy tính,Mạng máy tính; Security measures,Các biện pháp an ninh